Increasing the contrast and accuracy of localization of objects of interest on orthophotomaps of the terrain built from distorted images from an unmanned aerial vehicle - A. S. Zakhlebin; M. I. Kuryachiy; V. V. Kapustin; A. V. Kamenskiy; A. K. Movchan (Омский научный вестник)
In this article, we will consider and compare methods for eliminating distortions in the original images obtained from an unmanned aerial vehicle. The main goal of these methods is to increase the contrast and accuracy of determining the coordinates of objects of interest relative to the background. To conduct the study, aerial work is performed, during which initial images of the underlying surface with different exposure times are obtained, as well as data from the unmanned aerial vehicle navigation module. Further, cameral processing of the received materials is carried out. The exact centers for photographing each image are calculated and orthophotomaps of the area are built. Then we have evaluated the contrast and accuracy of determining the coordinates of objects of interest relative to the background on the orthophotomaps of the area built from the original and restored images using various methods.